Histologic Development of the Human Fovea From Midgestation to Maturity - Hendrickson, Anita; Possin, Daniel; Vajzovic, Lejla; Toth, Cynthia A. (American journal of ophthalmology, 2012)
To describe the histologic development of the human central retina from fetal week (Fwk) 22 to 13 years. Retrospective observational case series. Retinal layers and neuronal substructures were delineated on foveal sections of fixed tissue stained in azure II–methylene blue and on frozen sections immunolabeled for cone, rod, or glial proteins. Postmortem tissue was from 11 eyes at Fwk 20–27; 8 eyes at Fwk 28–37; 6 eyes at postnatal 1 day to 6 weeks; 3 eyes at 9 to 15 months; and 5 eyes at 28 months to 13 years. At Fwk 20–22 the fovea could be identified by the presence of a single layer of cones in the outer nuclear layer. Immunolabeling detected synaptic proteins, cone and rod opsins, and Müller glial processes separating the photoreceptors. The foveal pit appeared at Fwk 25, involving progressive peripheral displacement of ganglion cell, inner plexiform, and inner nuclear layers. The pit became wider and shallower after birth, and appeared mature by 15 months. Between Fwk 25 and Fwk 38, all photoreceptors developed more distinct inner and outer segments, but these were longer on peripheral than foveal cones. After birth the foveal outer nuclear layer became much thicker as cone packing occurred. Cone packing and neuronal migration during pit formation combined to form long central photoreceptor axons, which changed the outer plexiform layer from a thin sheet of synaptic pedicles into the thickest layer in the central retina by 15 months. Foveal inner and outer segment length matched peripheral cones by 15 months and was 4 times longer by 13 years. These data are necessary to understand the marked changes in human retina from late gestation to early adulthood. They provide qualitative and quantitative morphologic information required to interpret the changes in hyper- and hyporeflexive bands in pediatric spectral-domain optical coherence tomography images at the same ages.